Evaluación de insecticidas biorracionales como estrategia mip para controlar plagas del Chocho (lupinus mutabilis), Parroquia Aláquez, Barrio Colayapamba, Cantón Latacunga, Cotopaxi. 2017-2018. - Gómez Carranza, Andrés Sebastián (2018)
Evaluation of bio-rational insecticides as an IPM strategy to control cholera pests (Lupinus mutabilis), Aláquez parish, Colayapamba neighborhood, Latacunga county, Cotopaxi. 2017-2018. In this research called En In this research called evaluation of bio-rational insecticides to control the main pests of lupine (Lupinus mutabilis) in the Parish Aláquez, Barrio Colayapamba, Cantón Latacunga ". The objectives in this study were: To determine the incidence of pests of each treatment in the different phenological phases of the crop and to select the best insecticide to control the main pests of the lupine. To carry out these objectives, a design of Completely Random Blocks (DBCA) was proposed with six treatments, each treatment with three repetitions giving a total of eighteen experimental units in an area of 700 m2. The statistical analyzes of the data were performed using Infostat (IS) statistical software, for the effect of the variable "insecticide" in the percentage of control of the pests, the variance analysis (ADEVA) was carried out. The results of this study revealed that in the first phenological stage at 15 days we can see the insecticide that had the lowest incidence of pests is T3 (Neem) and T4 (Chemical) with an average of 4.69%, and in the second stage at 35 days was the treatment T3 (Neem) with an average of 1.27% and in the third stage phenology at 70 days was the treatment T3 (Neem) with an average of 6.28% and in the last phenological stage at 120 days that it was in the sheathing, the smallest attack of larvae presented in the treatment T3 (Neem) both treatments had an average of 24.24%. It is concluded that the best insecticide for the control of the main pest pests (borers, cutters, bed bugs, wire worm, coleoptera) was the neem treatment (T3) due to its active ingredient and the T4 chemical treatment showed the highest degree of efficiency in the control of major pests.